Effect of Dietary Ramie Powder (Boehmeria nivea) at Various Levels on Growth Performance, Carcass and Meat Qualities, Biochemical Indices, and Antioxidative Capacity of Linwu Ducks - Lin, Qian; Liu, Yang; Wang, Xin; Wang, Yan-Zhou; Huang, Peng; Liu, Chun-Jie; Liao, Li-Ping; Li, Ying-Hui; Fan, Zhi-Yong; Zeng, Jian-Guo; Zhu, Si-Yuan; Qiu, Hua-Jiao (Frontiers in Physiology, 2022)
Current experiment was designed to check the effect of dietary supplementation of ramie powder on the growth performance, carcass and meat qualities and antioxidative capacity of Linwu ducks. A total of 312 ducks at 21-day-age were equally divided into 4 groups, fed with control diet, control diet supplemented of 3%, 6%, or 12% ramie powder, respectively. The results showed that dietary supplementation of 6% and 12% ramie powder increased the final weight and daily body weight gain (P<0.05), and dietary supplementation of 6% ramie improved the cooking loss of the leg meat 45-mins-postmortem compared with the control group (P<0.05). Moreover, dietary supplementation of 6% ramie powder promoted the antioxidative capacity of the ducks by increasing the serum activities of superoxide dismutase and glutathione (P<0.05), as well as the mRNA expressions of glutathione peroxidase 1 in the breast meat and superoxide dismutase 1 in the leg meat (P<0.05). This experiment demonstrated that dietary supplementation of ramie powder showed beneficial efficacy on the growth performance of Linwu ducks. It corroborated the potential of dietary ramie being used as poultry feed ingredient and suggested that 6% was the proper supplementation rate of ramie powder in Linwu ducks’ feed.